Modeling of protein hydration dynamics is supported by THz spectroscopy of highly diluted solutions - Woods, Kristina N. (Frontiers in Chemistry, 2023)
In this investigation, we report the effect on the microscopic dynamics and interactions of the cytokine interferon gamma (IFN-γ) and antibodies to IFN-γ (anti-IFN-γ) and to the interferon gamma receptor 1 (anti-IFNGR1) prepared in highly dilute (HD) solutions of initial proteins. THz spectroscopy measurements have been conducted as a means to analyze and characterize the collective dynamics of the HD samples. MD simulations have also been performed that have successfully reproduced the observed signatures from experimental measurement. Using this joint experimental-computational approach we determine that the HD process associated with the preparation of the highly diluted samples used in this investigation induces a dynamical transition that results in collective changes in the hydrogen-bond network of the solvent. The dynamical transition in the solvent is triggered by changes in the mobility and hydrogen-bonding interactions of the surface molecules in the HD samples and is characterized by dynamical heterogeneity. We have uncovered that the reorganization of the sample surface residue dynamics at the solvent-protein interface leads to both structural and kinetic heterogeneous dynamics that ultimately create interactions that enhance the binding probability of the antigen binding site. Our results indicate that the modified interfacial dynamics of anti-IFN-γ and anti-IFGNR1 that we probe experimentally are directly associated with alterations in the complementarity regions of the distinct antibodies that designate both antigen-antibody affinity and recognition.